Manajemen Konflik di Sekolah - Eko Suncaka (Departement of Mathematics Education, 2023)
The purpose of this research is to find out the conflict management that exists in schools. The research uses a literature study where all information is obtained from articles and books. The results and discussion obtained can be described that the school principal as an administrator (school manager) and educational leader (educational leader) should be able to consider various existing conflict management strategies. One thing that is recommended is to start from a passive attitude to an active orientation, and it really depends on the level of maturity of the parties experiencing the conflict. An understanding of how to change the attitudes and behavior of people who are led and also matters relating to power or authority is needed to better master conflict management. Another thing to consider in using conflict management strategies is the source of the cause. In principle, the principal must have the power and authority as an educational leader. He must be able to utilize the power that is in him and be able to take advantage of the authority that is in him to direct the attitudes and behavior of subordinates. Implicitly it cannot be generalized that conflict is something that is detrimental or beneficial. In order for conflict to increase the performance and productivity of an organization, the leader of the organization is required to have the ability to manage conflict. There are several conflict management techniques in all situations, where each approach has advantages and disadvantages. Conflict needs to be resolved in a way that is appropriate and appropriate against the background of the conflict. The causes of conflict are not solely internal to the organization but also external to the organization.